HYPOTHYROIDISM FOLLOWING THYROID SURGERY - M. Lankarani; H. Mahmoodzadeh; N. Poorpezeshk; B. Soleimanpour; V. Haghpanah; R. Heshmat; S. Aghakhani P. Shooshtarizadeh (Acta Medica Iranica, 2008)
Postsurgical hypothyroidism and its incidence has not been fully investigated. In this study, the incidence of hypothyroidism and its possible risk factors at Shariati Hospital was assessed. One hundred and two patients with benign thyroid diseases, who had undergone thyroidectomy, were investigated with regards to thyroid function profile during period of one year after the operation every three months with post-operative sample as the baseline. Hypothyroidism was developed in 36 patients (35.2%) on average 5 ± 3.2 months after surgery. Factors such as increased age, operation type, histopathologic type, underlying disease, lymphocytic infiltration and use of levothyroxine before surgery were associated with the increased incidence of hypothyroidism. It seems that use of indicators such as Graves' disease and lymphocytic infiltration in pathologic specimens should be helpful in projecting the potential occurrence of hypothyroidism in patients undergoing thyroidectomy.